Numerical solutions of free convection boundary layer flow on a horizontal plate - Leli Deswita; Roslinda Nazar; Rokiah Ahmad; Anuar Ishak; Ioan Pop (Penerbit ukm, 2009)

(untitled)
In this paper numerical solutions are obtained for the steady laminar free convection boundary layer flow on a horizontal plate with variable wall temperature. The governing nondimensional boundary layer equations are transformed into ordinary differential equations using similarity transformation, which are then solved numerically using an implicit finite difference scheme known as the Keller-box method. The numerical results for different values of the Prandtl number Pr and the constant m representing the power index are obtained. The effects of various values of Prandtl number Pr and m on the velocity profiles, temperature profiles, skin friction and heat transfer coefficients are presented and discussed